Prenatal Diagnosis of Complex Copy Number Variants in the Fetus and Associated Cytogenetic Findings in Parents - Wei Wang; Jing Wang; Ye Shi; Bin Zhang (IMR Press, 2023)
Background: Co-occurrence of complex copy number variants (CNVs) is associated with more severe clinical expressivity of known syndromes. Few studies discuss diagnosis and genetic counseling for fetuses identified with multiple CNVs. This cohort study aims to summarize findings of complex copy number variants identified via prenatal diagnosis along with the results of parental studies. Methods: 2746 pregnant women were included and diagnosed by chromosomal microarray analysis (CMA) according to different clinical indications. A total of 12 fetuses were diagnosed with complex CNVs (a fetus identified with two or more CNVs simultaneously). Parental analysis was performed by CMA, G-band karyotype analysis, and whole-genome low-coverage mate-pair sequencing (WGL-MPS) based on the size of the fetal imbalances and method resolution. Results: Fetuses carrying complex CNVs were identified as being 0.4% (12/2746) in our cohort. The parental validation study was performed in 8 of 12 complex CNVs cases with the permission of the patients. The primary results suggested that 62.5% (5 out of 8) of fetuses with complex CNVs were from parental inheritance. In these cases, 4 out of 5 were derived from maternal or paternal balanced translocation carriers. Recurrent spontaneous abortion was found in balanced translocation carrier family. Conclusion: In this study, in 4/8 of the fetuses detected with complex CNVs was inherited from a parental balanced translocation. Given the risk of parental balanced rearrangements when fetal complex CNVs are identified, genetic counseling for future pregnancies may be useful for these families.